2009
DOI: 10.18352/lq.7957
|View full text |Cite
|
Sign up to set email alerts
|

Missing Web References — A Case Study of Five Scholarly Journals

Abstract: The present study attempts to ascertain the proportion of missing web references of 5-10-year-old research papers of the five leading open access (OA) journals in library and information science. The results suggest that the number of web citations has increased from 41.60% of all citations in 1998 to 53.32% in 2002. But a substantial quantity of web citations (32.09%) was found to be missing. The percentage of missing web citations goes on increasing with each passing year -ten-year-old publications having th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…The results revealed that within 2 months of publication of the first 2006 issue of each journal, 10 per cent of web citations were inactive and the rate of inactivity rose to 38 per cent after 7 years. Bhat (2009) analyzed the proportion of missing web references of research papers in library and information science. The results revealed that the number of web citations has increased from 41.60 per cent in 1998 to 53.32 per cent in 2002, whereas 32 per cent of them were found to be missing, with error 404 contributing to about 74 per cent of total missing web citations.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The results revealed that within 2 months of publication of the first 2006 issue of each journal, 10 per cent of web citations were inactive and the rate of inactivity rose to 38 per cent after 7 years. Bhat (2009) analyzed the proportion of missing web references of research papers in library and information science. The results revealed that the number of web citations has increased from 41.60 per cent in 1998 to 53.32 per cent in 2002, whereas 32 per cent of them were found to be missing, with error 404 contributing to about 74 per cent of total missing web citations.…”
Section: Review Of Literaturementioning
confidence: 99%
“…They further concluded that the .edu domain was the most stable domain with the highest percentage of stability. Bhat (2009) analyzed the Web references in five leading journals in the field of Library and Information Science for over five years from 1998 to 2002. The results revealed that the growth in Web citations increased from 41.6% in 1998 to 53.32% in 2002, whereas almost 32% of them were found to be missing, error 404 being the leading error associated with them contributing to about 74% of the total missing Web citations.…”
Section: Literature Reviewmentioning
confidence: 99%